COLL 613-Studies on the vapor-phase photo-oxidation of methanol over nano-size titania clusters dispersed in MCM-41 mesoporous silica - Kumar, Dharmesh; Bhattacharyya, Kaustav; Tripathi, Arvind; Varma, Salil; Gupta, Narendra M. (Abstracts of Papers of the American Chemical Society, 2006)

Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.